Quality of Health Service Outpatient Unit UPT Puskesmas Ciputat Timur Tahun 2019 - Della Dwi Ayu; Fajar Ariyanti (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
One of the SDGs targets in achieving UHC is increasing access to quality essential health services. Puskesmas is the front line in providing essential health services in the community. However, several complaints were still found in the health services provided, which also decreased public access to the Puskesmas. This study aims to determine the quality of outpatient health services at the UPT Puskesmas Ciputat Timur in 2019. This research is an evaluation study using a descriptive-analytical survey method with a quantitative approach with a cross-sectional study design. The sample determination was based on the Probability Proportionate to Size sampling technique with a total sample of 341 samples according to the sample table from Krejcie and Morgan. Data were collected using a questionnaire with two methods of measuring service quality, namely Servqual and Community Satisfaction Index, and using univariate data analysis. The results of this study stated that outpatient satisfaction at the UPT Puskesmas Ciputat Timur was 2.16 (satisfactory) based on the servqual concept and 76.47 (good) based on the concept of community satisfaction index. This study concludes that the quality of outpatient health services at the UPT Puskesmas Ciputat Timur is good, although several items still need to be improved. Suggestions are needed to make information boards for patient registration requirements, increase discipline in-service time, make persuasive stickers or posters, add RM distribution officers, publish IKM results annually through the website and add waiting room seats for patients and their families.